PENGARUH KEMASAN TERHADAP MUTU SALE PISANG RAJA (Musa X paradisiaca AAB) SELAMA PENYIMPANAN: (The Effect of Packaging to Quality Sale “Raja” Banana (Musa X paradisiaca AAB) During Storage) - Andi Nur Faidah Rahman; Meta Mahendradatta; Jusmiati Effendi (Hasanuddin University Food Science and Technology Study Program, 2018)
Sale raja banana are foods processed by mature banana which have been through the drying process. During storage, quality of sale raja banana decreased in terms of chemical composition and organoleptics. It is needed a method to maintain the quality of sale raja banana during storage by applying packaging technology. The purpose of this study was to determine the effect of packaging methods (without packaging, HDPE packaging and HDPE vacuum packaging) and storage time on the chemical composition and organoleptic quality of sale raja banana. The design of this study consisted of two factors: packaging using three treatment levels (without packaging, HDPE packaging, and HDPE vacuum packaging) and storage time with five levels of treatment (0, 7, 14, 21, and 28 days). Data was processed using factorial Completely Randomized Design (CRD) with three replications. The chemical parameters analyzed were water content, ash content, reducing sugar, pH, and organoleptic tests (including color, aroma, taste and texture). The results showed that the storage of sale raja banana with HDPE vacuum packaging for 28 days gave the best results for all parameters.